A study of the partitioning of the first-order reduced density matrix according to the theory of atoms in molecules - Alcoba, D.R. (2005)
This work describes a simple spatial decomposition of the first-order reduced density matrix corresponding to an N -electron system into first-order density matrices, each of them associated to an atomic domain defined in the theory of atoms in molecules. A study of the representability of the density matrices arisen from this decomposition is reported and analyzed. An appropriate treatment of the eigenvectors of the matrices defined over atomic domains or over unions of these domains allows one to describe satisfactorily molecular properties and chemical bondings within a determined molecule and among its fragments. Numerical determinations, performed in selected molecules, confirm the reliability of our proposal. © 2005 American Institute of Physics.